Proses Pengolahan dan Pemurnian Bijih Tembaga dengan Cara Konvensional dan Biomining - Anton Sudiyanto (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Indonesia has ore reserves of copper (Cu) which is very large, most of the reserves with porphyry Cu content in the ore vary between 0.1 - 2%. In addition to Cu, usually ore associated with other metals such as gold (A), silver (Ag) and rare metals such as Palladium (Pd ), Selenium ( Se ) and others. Several types of Cu ore there is Bornite (Cu5FeS4), Calcopyrite (CuFeS2), Covellite (CuS) with some impurities such as pyrite (FeS2), Magnetite (Fe3O4), hematite (Fe2O3), or Quartz (SiO2). Caused most of the sulfide minerals in the conventional treatment (physical - chemical ) would be more effective if the initial process is